2017
DOI: 10.1017/s1473550417000167
|View full text |Cite
|
Sign up to set email alerts
|

Could photosynthesis function on Proxima Centauri b?

Abstract: Could oxygenic and/or anoxygenic photosynthesis exist on planet Proxima Centauri b? Proxima Centauri (spectral type – M5.5 V, 3050 K) is a red dwarf, whereas the Sun is type G2 V (5780 K). The light regimes on Earth and Proxima Centauri b are compared with estimates of the planet's suitability for Chlorophyll a (Chl a) and Chl d-based oxygenic photosynthesis and for bacteriochlorophyll (BChl)-based anoxygenic photosynthesis. Proxima Centauri b has low irradiance in the oxygenic photosynthesis range (400–749 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 150 publications
(437 reference statements)
7
46
0
Order By: Relevance
“…m for a late-type M-dwarf analogous to TRAPPIST-1 (T = 2500 K). These numbers are in reasonable agreement with the corresponding values of 185 m and 10 m calculated for Earth and Proxima b, respectively(Ritchie et al 2018, …”
supporting
confidence: 89%
See 1 more Smart Citation
“…m for a late-type M-dwarf analogous to TRAPPIST-1 (T = 2500 K). These numbers are in reasonable agreement with the corresponding values of 185 m and 10 m calculated for Earth and Proxima b, respectively(Ritchie et al 2018, …”
supporting
confidence: 89%
“…Thus, communities circulating in this layer are theoretically 3 This result seems compatible with the detection of microalgae at depths of 285 m on Earth (Valiela 2015, Chapter 3.1). 4 As per empirical data and theoretical constraints, F C ∼ 0.01 µmol m −2 s −1 is compatible with anoxygenic photoautotrophs (Raven et al 2000;Manske et al 2005), but the prior conservative limit is adopted for comparison against Ritchie et al (2018). capable of survival and growth.…”
Section: Critical Depth and Compensation Depthmentioning
confidence: 91%
“…Ritchie et al. () discussed the possibility of a photosynthetic ecology existing on Proxima Centauri b which appears to be a viable habitable planet. Several researches addressed the evaluation of the survival capacity of extremophile/extremotolerant organisms when facing harsh conditions, including those of outer space or of simulated Martian environment (Duarte et al.…”
Section: Extremophile Microalgae In the Context Of Astrobiologymentioning
confidence: 99%
“…Although they radiate less photons in the Photo-synthetically Active Radiation (PAR) waveband (400-700nm) than is incident on Earth, there is still enough PAR flux to support Earth-like plant life (Gale and Wandel,2017). Ritchie et al (2018) made theoretical estimates and laboratory measurements of the photosynthesis of different species of algae exposed to radiation levels which could be expected at the Sub-stellar points of TLPs. They concluded that the PAR incident on TLPs may produce high levels of basic plant productivity: from 13-22% of what would be expected on Earth.…”
Section: Could Tlps Support Oxygenic Photosynthesis and Oxygen-rich Amentioning
confidence: 99%